Plz solve this sum

Asked by  | 27th Jan, 2010, 08:34: AM

Expert Answer:

Let u = xy and v = yx.

ln u = y lnx

(1/u)du/dx = y/x + lnx dy/dx

du/dx = xy (y/x + lnx dy/dx)

ln v = x ln y

dv/dx = yx (lny + (x/y)dy/dx )

Now du/dx + dv/dx = 0

xy (y/x + lnx dy/dx) = -yx (lny + (x/y)dy/dx )

This gives after simplification,

dy/dx = (-yxlny - xy-1y)/(xylnx + yx-1x)

Regards,

Team,

TopperLearning.

Answered by  | 27th Jan, 2010, 09:58: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.